Pengaruh Relationship Marketing Terhadap Loyalitas Debitur Di Mediasi oleh Kualitas Hubungan, Studi Empiris Di Bank Sumatera Bagian Selatan - Silke Sachanovrissa (UNIVED Press, 2023)
One of the strategies implemented by the banking sector is to apply the concept of relationship marketing (RM). Relationship marketing (RM) is very helpful for companies in fostering good relationships with customers, debtors, and shareholders. In this study, the direction of the research was to examine how important the quality of the relationship between regional bank customers (Bengkulu Bank, Jambi Bank and Bank Lampung) had a positive impact in increasing the relationship marketing / RM dimensions (customer trust, customer commitment, and communication) to loyalty. This study uses an explanatory survey approach with a quantitative analysis approach. The population in this study were debtor customers at three regional-owned banks, namely Bengkulu Bank, Jambi Bank and Lampung Bank. The number of research samples were 520 respondents. The sampling method used a purposive sampling approach. The analytical tool used is Structural Equation Modeling (SEM) using the LISREL 8.7 program. In this study, the researcher found novelty, namely with regard to the dimensions in the relationship quality variable. Where in previous research in marketing there were 2 dimensions, namely respect and rapport. Meanwhile, this study adds a personality trait dimension.